Profilaktyka nowotworów u kobiet w Polsce. Sukces, czy niepowodzenie? Opinie pacjentów, lekarzy i instytucji odpowiedzialnych za stan zdrowia – metaanaliza = Prevention of cancer in women in Poland. Success or failure? Opinions of patients, physicians and institutions responsible for health – meta-analysis - Kołłątaj, Witold; Karwat, Irena Dorota; Kołłątaj, Barbara; Piecewicz-Szczęsna, Halina; Sowa, Magda (Journal of Education, Health and Sport, 2016)
Kołłątaj Witold, Karwat Irena Dorota, Kołłątaj Barbara, Piecewicz-Szczęsna Halina, Sowa Magda. Profilaktyka nowotworów u kobiet w Polsce. Sukces, czy niepowodzenie? Opinie pacjentów, lekarzy i instytucji odpowiedzialnych za stan zdrowia – metaanaliza = Prevention of cancer in women in Poland. Success or failure? Opinions of patients, physicians and institutions responsible for health – meta-analysis. Kołłątaj Witold, Karwat Irena Dorota, Kołłątaj Barbara, Piecewicz-Szczęsna Halina, Sowa Magda. Profilaktyka nowotworów u kobiet w Polsce. Sukces, czy niepowodzenie? Opinie pacjentów, lekarzy i instytucji odpowiedzialnych za stan zdrowia – metaanaliza = Prevention of cancer in women in Poland. Success or failure? Opinions of patients, physicians and institutions responsible for health – meta-analysis. Journal of Education, Health and Sport. 2016;6(6):318-328. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55608 http://ojs.ukw.edu.pl/index.php/johs/article/view/3585 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016. Profilaktyka nowotworów u kobiet w Polsce. Sukces, czy niepowodzenie? Opinie pacjentów, lekarzy i instytucji odpowiedzialnych za stan zdrowia – metaanaliza Prevention of cancer in women in Poland. Success or failure? Opinions of patients, physicians and institutions responsible for health – meta-analysis Witold Kołłątaj1, Irena Dorota Karwat2, Barbara Kołłątaj2, Halina Piecewicz‑Szczęsna2, Magda Sowa3 1Klinika Endokrynologii i Diabetologii Dziecięcej, Uniwersytet Medyczny w Lublinie 2Katedra i Zakład Epidemiologii i Metodologii Badań Klinicznych, Uniwersytet Medyczny w Lublinie 3Katedra i Zakład Zdrowia Publicznego, Uniwersytet Medyczny w Lublinie Adres do korespondencji: dr hab. n. med. Witold Kołłątaj Klinika Endokrynologii i Diabetologii Dziecięcej z Pracownią Metaboliczną UM w Lublinie ul. Profesora Antoniego Gębali 6, 20-093 Lublin e-mail: wk@data.pl Słowa kluczowe: nowotwory, profilaktyka, kobiety, opinie, metaanaliza. Keywords: cancer prevention, women, opinions, meta-analysis. Streszczenie Wstęp Choroby nowotworowe od wielu lat stanowią w Polsce drugą przyczynę zgonów. Co roku, z tego powodu, umiera niemal 100 000 osób, a liczba zgonów ma tendencję rosnącą. Wyniki leczenia nowotworów w Polsce są gorsze, niż w krajach Europy, diagnostyka często spóźniona, a profilaktyka niewystarczająco skuteczna. W celu poprawy stanu zdrowa społeczeństwa, rosną nakłady na leczenie i profilaktykę. W Polsce profilaktykę koordynuje Narodowy Program Zwalczania Chorób Nowotworowych. Cel pracy Celem pracy jest próba rzetelnej oceny stanu profilaktyki nowotworów u kobiet w Polsce, uwzględniającej opinie zarówno organów odpowiedzialnych za ochronę zdrowia, lekarzy, organów kontroli, jak i pacjentów. Materiał i metody Materiał stanowiły sprawozdania podmiotów odpowiedzialnych za realizację profilaktyki nowotworów u kobiet, akty prawne, publikacje naukowe oceniające realizację profilaktyki nowotworów u kobiet w Polsce oraz dane z Audytu Społecznego Narodowych Programów Profilaktyki Nowotworowej. Wyniki i omówienie Ministerstwo Zdrowia oraz Narodowy Fundusz Zdrowia publikują dane, które podkreślają osiągnięcia profilaktyki nowotworów u kobiet w Polsce, natomiast opinie fachowych pracowników służby zdrowia (wyrażone w konkluzji realizowanych prac badawczych) oraz pacjentów wskazują na znaczne dysproporcje między założeniami programów profilaktycznych a ich faktyczną realizacją. Wśród niedociągnięć wymieniane są przede wszystkim niewystarczające działania edukacyjne, niedociągnięcia organizacyjne (nieuwzględnianie w harmonogramie badań grafiku pracy pacjentek, niewłaściwe informowanie o terminach badań, błędy w dystrybucji wezwań na badanie, nieprzyjazne kobietom warunki badania) oraz inne czynniki, które kobiety określają, jako podważające zaufanie do jakości badania. Najwięcej negatywnych emocji budzi stan komunikacji z grupami docelowymi kobiet oraz zaniedbania z zakresu edukacji. Wnioski Optymistyczne oceny osiągnieć Narodowego Programu Zwalczania Chorób Nowotworowych ogłoszone przez Ministerstwo Zdrowia nie znajdują pełnego pokrycia w opiniach zarówno organów kontrolnych, pacjentów, jak i środowiska medycznego. Liczne negatywne oceny programów profilaktycznych oraz sugestie głębokich reform Narodowego Programu Zwalczania Chorób Nowotworowych nie mają wpływu na plany Ministerstwa Zdrowia. Celowym wydaje się analiza przyczyn takiego stanu rzeczy, kiedy to opinie świata nauki, wyrażane między innymi w publikacjach naukowych, nie skłaniają Ministerstwa Zdrowia do refleksji lub przynajmniej do wszczęcia polemiki ze środowiskiem naukowym i lekarzami praktykami. Summary Introduction For many last years, neoplastic diseases have been the second cause of death in Poland. Every year, such diseases are the reasons for almost 100 000 cases of death. The mortality because of neoplasms has got the increasing tendency. The results of cancer treatment in Poland are worse than in many European countries, diagnoses often delayed and the prevention insufficiently effective. In order to improve the health status of Polish population, the expenditures on treatment and prevention have been slightly raised. In Poland, the prevention is coordinated by the National Cancer Control Program. Aim The aim of the study was the assessment of cancer prevention in women in Poland, taking into account opinions of both Polish Ministry of Health, audit institutions, patients and the medical community. Material and methods The material consists of the reports of entities responsible for the implementation of cancer prevention in women, legislative acts, scientific publications evaluating the implementation of the prevention of cancer in women in Poland as well as data from the National Social Audit Program Cancer Prevention. Results and Discussion While the Ministry of Health and the National Health Fund publish data that highlight the achievements, medical community’s opinions (expressed as the conclusions of ongoing researches) as well as the opinions of patients show a significant disparity between the objectives of prevention programs and their actual implementations. Among mentioned shortcomings there are: educational and organizational negligence (working hours of facilities dealing with the prevention are coinciding with the working hours of women, incorrect information about the terms of preventive procedures, improper schemes of distribution of calls for screenings, embarrassing and unpleasant conditions of screenings) as well as other factors that women define as those that prejudice them to take part in such medical procedures. The most negative emotions concern the mechanisms of communication between screening centers and the target groups of women and educational negligence. Conclusions 1. The optimistic assessment of achievements of the National Cancer Control Program proclaimed by the Polish Ministry of Health are not fully covered in the opinions of audit institutions, patients and the medical community. 2. Numerous negative opinions concerning prevention programs and suggestions of deep reform of the National Cancer Control Program have no effect on the plans of the Polish Ministry of Health. 3. It seems appropriate to analyze the causes of this state of affairs, when the opinions expressed by medical community, among others, published as scientific publications, do not tend to reflect the Ministry of Health, or at least to initiate a polemic with the medical-scientific experts and practitioners. Journal of Education, Health and Sport. 2016;6(6):318-328. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55608 http://ojs.ukw.edu.pl/index.php/johs/article/view/3585 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016. Profilaktyka nowotworów u kobiet w Polsce. Sukces, czy niepowodzenie? Opinie pacjentów, lekarzy i instytucji odpowiedzialnych za stan zdrowia – metaanaliza Prevention of cancer in women in Poland. Success or failure? Opinions of patients, physicians and institutions responsible for health – meta-analysis Witold Kołłątaj1, Irena Dorota Karwat2, Barbara Kołłątaj2, Halina Piecewicz‑Szczęsna2, Magda Sowa3 1Klinika Endokrynologii i Diabetologii Dziecięcej, Uniwersytet Medyczny w Lublinie 2Katedra i Zakład Epidemiologii i Metodologii Badań Klinicznych, Uniwersytet Medyczny w Lublinie 3Katedra i Zakład Zdrowia Publicznego, Uniwersytet Medyczny w Lublinie Adres do korespondencji: dr hab. n. med. Witold Kołłątaj Klinika Endokrynologii i Diabetologii Dziecięcej z Pracownią Metaboliczną UM w Lublinie ul. Profesora Antoniego Gębali 6, 20-093 Lublin e-mail: wk@data.pl Słowa kluczowe: nowotwory, profilaktyka, kobiety, opinie, metaanaliza. Keywords: cancer prevention, women, opinions, meta-analysis. Streszczenie Wstęp Choroby nowotworowe od wielu lat stanowią w Polsce drugą przyczynę zgonów. Co roku, z tego powodu, umiera niemal 100 000 osób, a liczba zgonów ma tendencję rosnącą. Wyniki leczenia nowotworów w Polsce są gorsze, niż w krajach Europy, diagnostyka często spóźniona, a profilaktyka niewystarczająco skuteczna. W celu poprawy stanu zdrowa społeczeństwa, rosną nakłady na leczenie i profilaktykę. W Polsce profilaktykę koordynuje Narodowy Program Zwalczania Chorób Nowotworowych. Cel pracy Celem pracy jest próba rzetelnej oceny stanu profilaktyki nowotworów u kobiet w Polsce, uwzględniającej opinie zarówno organów odpowiedzialnych za ochronę zdrowia, lekarzy, organów kontroli, jak i pacjentów. Materiał i metody Materiał stanowiły sprawozdania podmiotów odpowiedzialnych za realizację profilaktyki nowotworów u kobiet, akty prawne, publikacje naukowe oceniające realizację profilaktyki nowotworów u kobiet w Polsce oraz dane z Audytu Społecznego Narodowych Programów Profilaktyki Nowotworowej. Wyniki i omówienie Ministerstwo Zdrowia oraz Narodowy Fundusz Zdrowia publikują dane, które podkreślają osiągnięcia profilaktyki nowotworów u kobiet w Polsce, natomiast opinie fachowych pracowników służby zdrowia (wyrażone w konkluzji realizowanych prac badawczych) oraz pacjentów wskazują na znaczne dysproporcje między założeniami programów profilaktycznych a ich faktyczną realizacją. Wśród niedociągnięć wymieniane są przede wszystkim niewystarczające działania edukacyjne, niedociągnięcia organizacyjne (nieuwzględnianie w harmonogramie badań grafiku pracy pacjentek, niewłaściwe informowanie o terminach badań, błędy w dystrybucji wezwań na badanie, nieprzyjazne kobietom warunki badania) oraz inne czynniki, które kobiety określają, jako podważające zaufanie do jakości badania. Najwięcej negatywnych emocji budzi stan komunikacji z grupami docelowymi kobiet oraz zaniedbania z zakresu edukacji. Wnioski Optymistyczne oceny osiągnieć Narodowego Programu Zwalczania Chorób Nowotworowych ogłoszone przez Ministerstwo Zdrowia nie znajdują pełnego pokrycia w opiniach zarówno organów kontrolnych, pacjentów, jak i środowiska medycznego. Liczne negatywne oceny programów profilaktycznych oraz sugestie głębokich reform Narodowego Programu Zwalczania Chorób Nowotworowych nie mają wpływu na plany Ministerstwa Zdrowia. Celowym wydaje się analiza przyczyn takiego stanu rzeczy, kiedy to opinie świata nauki, wyrażane między innymi w publikacjach naukowych, nie skłaniają Ministerstwa Zdrowia do refleksji lub przynajmniej do wszczęcia polemiki ze środowiskiem naukowym i lekarzami praktykami. Summary Introduction For many last years, neoplastic diseases have been the second cause of death in Poland. Every year, such diseases are the reasons for almost 100 000 cases of death. The mortality because of neoplasms has got the increasing tendency. The results of cancer treatment in Poland are worse than in many European countries, diagnoses often delayed and the prevention insufficiently effective. In order to improve the health status of Polish population, the expenditures on treatment and prevention have been slightly raised. In Poland, the prevention is coordinated by the National Cancer Control Program. Aim The aim of the study was the assessment of cancer prevention in women in Poland, taking into account opinions of both Polish Ministry of Health, audit institutions, patients and the medical community. Material and methods The material consists of the reports of entities responsible for the implementation of cancer prevention in women, legislative acts, scientific publications evaluating the implementation of the prevention of cancer in women in Poland as well as data from the National Social Audit Program Cancer Prevention. Results and Discussion While the Ministry of Health and the National Health Fund publish data that highlight the achievements, medical community’s opinions (expressed as the conclusions of ongoing researches) as well as the opinions of patients show a significant disparity between the objectives of prevention programs and their actual implementations. Among mentioned shortcomings there are: educational and organizational negligence (working hours of facilities dealing with the prevention are coinciding with the working hours of women, incorrect information about the terms of preventive procedures, improper schemes of distribution of calls for screenings, embarrassing and unpleasant conditions of screenings) as well as other factors that women define as those that prejudice them to take part in such medical procedures. The most negative emotions concern the mechanisms of communication between screening centers and the target groups of women and educational negligence. Conclusions 1. The optimistic assessment of achievements of the National Cancer Control Program proclaimed by the Polish Ministry of Health are not fully covered in the opinions of audit institutions, patients and the medical community. 2. Numerous negative opinions concerning prevention programs and suggestions of deep reform of the National Cancer Control Program have no effect on the plans of the Polish Ministry of Health. 3. It seems appropriate to analyze the causes of this state of affairs, when the opinions expressed by medical community, among others, published as scientific publications, do not tend to reflect the Ministry of Health, or at least to initiate a polemic with the medical-scientific experts and practitioners.